Ophthalmology lecture notes - James, Bruce; Bron, Anthony (Wiley-Blackwell, 2011)
Beautifully illustrated throughout, Ophthalmology Lecture Notes concentrates on the most common eye problems that health practitioners are expected to diagnose and manage. The book begins with a brief introduction to ocular anatomy and eye examination, and then focuses on core conditions in ophthalmology.